Sesetan Traditional Village as Social and Art Aspect - Indra Wirawan, Komang (Green Publisher, 2022)
Sesetan Traditional Village is a village that is used as the basis for the preservation of traditions, customs, and Balinese culture. Sesetan PakramanVillage exists with various social, artistic and local culture approaches which include the social structure of Sesetan community, the arts and culture of Sesetan Village and the sekaa (traditional group) that bond as a local tradition, becoming an icon of Denpasar City. Sesetan Traditional Village has a wider area than the other area of South Denpasar Districts. Definitely, some clans or soroh of the Krama residents who live in Sesetan PakramanVillage are diverse. They consist of residents from different clans who form a community based on genealogical descent. When viewed from the structure of community, Sesetan Traditional Village consists of several krama, namely Krama Pengarep, Krama Tamiu, Krama Nyada, Krama Pangile. All these Krama are involved and they synergize each other in carrying outÂ ngayahÂ Â in the village, and assisting krama who are carrying out religious rituals. The existence of Sesetan Pakraman Village in its culture also has the uniqueness and diversity of art. This can be seen from Banjar Kaja to the Banjar Suwung Batan Kendal area which has a diversity of traditions, arts and culture, as well as aspects of religiosity framed in Hinduism. Such as, Omed-Omedan tradition, Ngelawang, the art of Calonarang dance drama and many others. It becomes interesting topic in this study regarding the socio, cultural and arts that developed in Sesetan Pakraman Village.